Pembaharuan Sistem Penentuan Untuk Klasifikasi Jenis Penyakit pada RSUD Sekayu Menggunakan Pendekatan Extreme Programming - Megawaty Megawaty; Nurul Huda (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
This research is done to create a system or software that can classify a type of disease suffered by the patient, by conducting anamnese technique, this technique is done in the early stages of the patient before the treatment of doctors, the examination is done by questioning the patient about the condition and complaints that the patient feels to know the health condition of the patient. The Anamnese stage is performed by the nurse station before the patient is directed to the doctor where it corresponds to the results of the Anamnese.  In the implementation of this stage is important for nurse station to direct the patient according to the patient's health condition with the Doctor who will handle the patient. But some diseases have similarities or similar symptoms but with different types of diseases, in the HOSPITAL Sekayu in Nurse station does not have a special system to classify the types of diseases of the patient this is what is the background of this research is made. The benefit is that the system can classify the types of diseases of patients according to the condition of the patient, helping nurse station to direct the patient to a classification of diseases suffered, as a storage media of the patient's medical record. The research was made to adopt the algorithm of K-Nearest Neighbor and the Extreme programming approach as a system development method.